Modalitas Kepemimpinan Kiai Dalam Membentuk Ummatan Wasathan (Ummat Moderat) - Ansori; Abu Khaer (CV Edujavare Publishing, 2023)
The leadership of the Kiai in the midst of a society that is considered conservative-traditionalist does not even have capital, and is incapable of exercising its power and leadership, as well as bringing the community to progress amidst differences both in religion, culture and religious sects. This study aims to examine the modalities of kiai leadership in forming a ummatan washatan (moderate ummat). This research uses a qualitative approach with a type of phenomenological research by looking at and listening to closer and detailed individual explanations and understanding. The results of the study show that Kyai Abdul Qodir Syam and Kiai Junaidi have a wealth of modalities/capitals, which are used to fight in the arena or realm in Bondowoso Regency with the aim of creating a conducive and peaceful society. There are four modalities owned by the two kiai. First, Economic Modality. Second, Social Modality, socially, Third. Cultural Modality, this modality is the most powerful and affects the other modalities, the two clerics have cultural differences, Kiai Abdul Qodir Syam is of blue blood descent, while Kiai Junaidi Mu'thi is not, but the two clerics have total commitment, loyalty as well as noble, charismatic and authoritative morals in carrying out his da'wah. Fourth, Symbolic Modality, symbolically, he is both a kiai, caretaker, Rais Syuriyah and Tanfidziyah PCNU.